2016
DOI: 10.1111/idh.12227
|View full text |Cite
|
Sign up to set email alerts
|

Oral health care‐related beliefs among Finnish geriatric home care nurses

Abstract: The nursing staff mostly believed that oral diseases are preventable and teeth can be retained in advanced age, but failed to recognize the value of dental knowledge and had little confidence in their ability to manage oral diseases. Improving the oral health-related knowledge and self-efficacy beliefs of nursing staff will require additional oral health education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
4
11
0
Order By: Relevance
“…The nurses have some knowledge about oral health-related problems among older people, but they are uncertain of their own skills when performing oral health practices for older people. The results of this study are in line with our previous study, which showed that nurses have limited oral health care knowledge about how to prevent dental diseases [9].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The nurses have some knowledge about oral health-related problems among older people, but they are uncertain of their own skills when performing oral health practices for older people. The results of this study are in line with our previous study, which showed that nurses have limited oral health care knowledge about how to prevent dental diseases [9].…”
Section: Discussionsupporting
confidence: 92%
“…When oral hygiene is registered into the daily treatment plan, the nurses make time for it. Many dental problems could be prevented by careful oral home care, but most of the nurses are uncertain about oral health practices and their self-efficacy is poor, which is same result we found in our previous study [9]. In addition, dental hygienists have been found to be willing to offer treatment, but their self-perceived competency was insufficient to carry out such measures [17].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Therefore, the consideration of OHRIs during the evaluation of service contents might depend mostly on the CMs knowledge of the matter or ability to use available guidelines. The general level of knowledge regarding oral health, ability to assess OHRIs during service planning and attitudes toward OHRIs might also have an effect on OHRIs during the evaluation of services.…”
Section: Discussionmentioning
confidence: 99%